Choice timing testing in the model of intellectual control subsystem of knowledge - Кравченко, Ольга Віталіївна; Плакасова, Жаннетта Миколаївна (Eastern-European Journal of Enterprise Technologies, 2012)
The analysis of existing adaptive learning systems is done. The advantages and disadvantages of adaptive systems are analyzed. A procedure for determining the time required to answer every question is suggested